2009
DOI: 10.1021/es900498r
|View full text |Cite
|
Sign up to set email alerts
|

XANES Evidence for Oxidation of Cr(III) to Cr(VI) by Mn-Oxides in a Lateritic Regolith Developed on Serpentinized Ultramafic Rocks of New Caledonia

Abstract: Although several laboratory studies showed that Mn-oxides are capable of oxidizing Cr(II) to Cr(VI), very few have reported evidence for such a reaction in natural systems. This study presents new evidence for this redox reaction between Cr(III) and Mn-oxides in a lateritic regolith developed on ultramafic rocks in New Caledonia. The studied lateritic regolith presents several units with contrasting amounts of major (Fe, Al, Si, and Mg) and trace (Mn, Cr, Ni, Co) elements, which are related to varying mineralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 57 publications
6
102
0
Order By: Relevance
“…However, the kinetics of Cr(III) oxidation by O 2 are extremely slow in natural settings (55,56). As a result, the most common oxidant for Cr(III) in Earth surface environments is Mn, in the form of Mn(III,IV) (hydr)oxides (15,(57)(58)(59)(60)(61). The kinetics of this process can be generally formulated as (62)(63)(64)(65):…”
Section: A Kinetic Framework For Cr(iii) and Mn(ii) Oxidationmentioning
confidence: 99%
“…However, the kinetics of Cr(III) oxidation by O 2 are extremely slow in natural settings (55,56). As a result, the most common oxidant for Cr(III) in Earth surface environments is Mn, in the form of Mn(III,IV) (hydr)oxides (15,(57)(58)(59)(60)(61). The kinetics of this process can be generally formulated as (62)(63)(64)(65):…”
Section: A Kinetic Framework For Cr(iii) and Mn(ii) Oxidationmentioning
confidence: 99%
“…Bearing in mind the geogenic source of Cr in the area the data indicate that the releasing process of this PHE within the shallow alluvial aquifer is conditioned by the geometry of the basin and subsequently by the groundwater flow and residence time. Chromium mobilization and groundwater enrichment in ophiolite related aquifers has been attributed by several authors to the oxidative action of Mn oxides as well as the alkaline water pH (Chardot et al, 2007;Cheng et al, 2011;Dermatas et al, 2014;Fandeur et al, 2009;Hseu and Iizuka, 2013). The process requires oxidation of Cr(III) present in primary minerals to Cr(VI) by Mn-oxides.…”
Section: Elemental Interactions In the Bedrock-soil-water Systemmentioning
confidence: 99%
“…The process requires oxidation of Cr(III) present in primary minerals to Cr(VI) by Mn-oxides. The subsequent release of Cr into the groundwater is controlled by adsorption reactions on the surface of Mn and Fe-oxides (Fandeur et al, 2009). Other authors have suggested a potential role of different electron acceptors and complex mineral phases such as layered double hydroxides and hydroxycarbonates in geogenic Cr oxidation and release from the solid phase under Mediterranean climate conditions (Langone et al, 2013).…”
Section: Elemental Interactions In the Bedrock-soil-water Systemmentioning
confidence: 99%
“…In the case of Cr, environmental concern is generally placed on the potential existence of Cr(VI), or possible oxidation of Cr(III) to Cr(VI), which mainly stipulate Cr toxicity (Fandeur et al 2009). In addition to the discussion in ''Pseudo-total element concentrations of weekly subsamples'', a routine analysis combining water extraction according to the two-stage batch test SFS-EN 12457-3 (L/S 10) and subsequent supernatant analysis by (1,5-)diphenylcarbatzide addition followed by absorbance quantification with a PerkinElmer (PerkinElmer, Norwalk, USA) Lambda 25 spectrophotometer was performed on two combined three-week ladle slag samples representative of the equivalent sampling period.…”
Section: Sequential Extraction and Mineralogical Characterizationmentioning
confidence: 99%